2015
DOI: 10.1016/j.ijhcs.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Decision support and vulnerability to interruption in a dynamic multitasking environment

Abstract: Using a microworld simulation of maritime decision making, we compared two decision support systems (DSS) in their impact upon recovery from interruption. The Temporal Overview Display (TOD) and Change History Table (CHT) -designed to support temporal awareness and change detection, respectively -have previously proven useful in improving situation awareness; however, evaluation of support tools for multitasking environments should not be limited to the specific aspects of the task that they were designed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…However, the domain of interruptions and multitasking is large and multifaceted. There is a clear dichotomy between routine tasks like the one presented in this study and problem solving tasks that have also been investigated (Hodgetts & Jones, 2006;Hodgetts, Tremblay, Vallières, & Vachon, 2015; P. L. Morgan & Patrick, 2013). Problem solving tasks require participants to be attentive and have a strong conceptual understanding of the problem they are trying to solve.…”
Section: Generalizabilitymentioning
confidence: 99%
“…However, the domain of interruptions and multitasking is large and multifaceted. There is a clear dichotomy between routine tasks like the one presented in this study and problem solving tasks that have also been investigated (Hodgetts & Jones, 2006;Hodgetts, Tremblay, Vallières, & Vachon, 2015; P. L. Morgan & Patrick, 2013). Problem solving tasks require participants to be attentive and have a strong conceptual understanding of the problem they are trying to solve.…”
Section: Generalizabilitymentioning
confidence: 99%
“…Unfortunately, few military domains currently incorporate multitasking assessment in their personnel selection process. Further, although multitasking training is not common in all military domains, some platforms currently exist that allow training to be adapted to the relevant context (Hodgetts et al, ; Kylesten & Nählinder, ). Mitchell and Driskell () have suggested that studies using job analyses could identify specific task requirements and cognitive skills needed to perform them.…”
Section: Discussionmentioning
confidence: 99%
“…Interruptions are also characteristic of demanding C2 operator work environments, which are dynamic and often involve situations that require frequent updates to colleagues or superiors (Hodgetts, Tremblay, Vallières, & Vachon, ). Because the main tasks of C2 operators are frequently changing, situational awareness tends to be limited, especially if changes occur when the operator's attention is directed toward another task and is therefore less likely to be noticed (Smallman & St. John, ; St. John & Smallman, ).…”
Section: Multitasking In Military Occupationsmentioning
confidence: 99%
See 1 more Smart Citation
“…By providing some level of control, microworlds may help to uncover generalizable causal interpretations necessary to validate theory. As in the case of any technology and/or new practice introduction, impact assessment it will be more realistically evaluated closer to the very often multitasking environment in which it will take place instead of the solo foci on the specific intervention [13].…”
Section: Introductionmentioning
confidence: 99%